Liver Specification in the Absence of Cardiac Differentiation Revealed by Differential Sensitivity to Wnt/β Catenin Pathway Activation - Haworth, Kim; Samuel, Lee; Black, Sarah; Kirilenko, Pavel; Latinkic, Branko (Frontiers in Physiology, 2019)
Embryonic precursors of liver and heart, whilst not sharing cellular origin, develop in close proximity through a dynamic series of inductive signalling events. During gastrulation anterior endoderm provides cardiogenic signals that act on adjacent mesoderm, resulting in induction of cardiac precursors. Subsequently cardiogenic mesoderm generates a FGF signal that acts on adjacent anterior endoderm to induce foregut organ specification. Additional signals such as BMP and Wnt provide further information required for liver specification. Most findings on liver specification were derived from mouse explant studies as well as experiments with Xenopus and zebrafish embryos. To address some of the limitations of these models, here we used two complementary ex-vivo models based on Xenopus embryos: pluripotent animal cap explants expressing GATA4 transcription factor and conjugates of gastrula-stage anterior endoderm with animal caps. We show that in these models liver specification is not sensitive to Wnt signalling manipulation, in contrast to the requirement for Wnt antagonism shown in vivo. FGF pathway is not necessary for GATA4-induced liver specification in animal cap explants but is required for prolonged period in sandwiches of anterior endoderm and animal caps. In contrast, BMP signalling is shown to be essential for GATA4-induced liver specification. Our findings may have implications for research on liver differentiation from embryonic stem cells.